'A Legal Limited Monarchy': Scottish Constitutionalism in the Union of Crowns, 1603–1707. Issue 2 (November 2015) - Bowie, Karin
<x content-type="archive" xml:space="preserve">Abstract</x> After the formation of the British composite monarchy in 1603, a distinctive pattern of Scottish constitutionalism emerged in which a desire to maintain the Scottish realm and church encouraged an emphasis on the limitation of the monarch by fundamental law, guaranteed by oaths. The Covenanters attempted to use the National Covenant and the 1651 coronation to force the king to maintain the Presbyterian church as defined by law. Restoration royalists emphasised the untrammelled power of the king, but in the Revolution of 1688-89, the Claim of Right was presented with the oath of accession as a set of conditions designed to re-establish the Scottish realm as a 'legal limited monarchy' with a Presbyterian church. Reforms in 1640-41, 1689-90 and 1703-4 placed statutory constraints on the royal prerogative. The making of the union relied on a reassertion of monarchical sovereignty, though Presbyterian unionists ensured that the new British monarch would be required to swear to uphold the church as established by law.